Successful retreatment with osimertinib after osimertinib-induced acute pulmonary embolism in a patient with lung adenocarcinoma: A case report. (2017) - Shiroyama, Takayuki; Hayama, Manabu; Satoh, Shingo; Nasu, Shingo; Tanaka, Ayako; Morita, Satomu; Morishita, Naoko; Suzuki, Hidekazu; Okamoto, Norio; Hirashima, Tomonori
Abstract: Pulmonary embolism (PE) can be life-threatening, and it is challenging to diagnose because of its nonspecific signs and symptoms. PE is also an important potential risk of osimertinib treatment, however, clinical courses regarding retreatment after osimertinib-induced acute pulmonary embolism remain unclear. We described a 77-year-old woman with postoperative recurrent lung adenocarcinoma who developed osimertinib-induced acute PE. She received apixaban and was later successfully retreated with osimertinib. This case suggests that retreatment with osimertinib after osimertinib-induced acute PE may be a treatment option when alternative therapeutic options are limited.